3D Unity Snake Game to Demonstrate Control System Transfer Function in Both Time and S-Domain - Sutiangso, John Allan (Journal of Interdisciplinary Perspectives, 2024)
The transfer function, a key concept in control systems, is essential for undergraduate engineering students. This study aims to enhance the understanding and appreciation of control systems by visualizing transfer functions. The 3D Snake Game, developed using the Unity game engine, offers a real-time gaming experience that integrates both s and t domain transfer functions. It follows the function path using activated quantization, time, and input settings. The game features customizable settings, including game speed, pin tail, joystick, and collision toggle. It is deployable on Android, computers, and the WebGL online platform. The game was highly effective in the target population of 48 Electronics Engineering students enrolled in Control Systems. The majority of students reported that the game helped them visualize control systems (83.04%, x̄=4.15, p=0.004), appreciate their applications (89.13%, x̄=4.46, p<0.001), and apply various transfer functions (85.65%, x̄=4.28, p<0.001). Additionally, the game was considered presentable (80.00%, x̄=4.00, p<0.001), aided in obtaining correct settling times (83.91%, x̄=4.20, p<0.001), and was user-friendly (82.50%, x̄=4.13, p<0.001). Overall, the 3D Snake Game is a valuable educational tool, enhancing the learning experience by making complex control system concepts more accessible and engaging for students. The game's ability to provide a hands-on, interactive approach to learning allows students to grasp theoretical concepts better and see their practical applications in real-time. This innovative teaching method improves comprehension and increases student interest and motivation in the subject matter.